2016
DOI: 10.15517/rbt.v64i1.23409
|View full text |Cite
|
Sign up to set email alerts
|

The easternmost tropical Pacific. Part II: Seasonal and intraseasonal modes of atmospheric variability

Abstract: This is Part II of a two-part review about climate and climate variability focused on the Eastern Tropical Pacific (ETP) and the Caribbean Sea (CS). Both parts are aimed at providing oceanographers, marine biologists, and other ocean scientists, a guiding base for ocean-atmosphere interaction processes affecting the CS, the ETP, and the waters of Isla del Coco. Isla del Coco National Park is a Costa Rican World Heritage site. Part I analyzed the mean fields for both basins and a larger region covering 25º S -3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 111 publications
1
42
0
12
Order By: Relevance
“…These findings help to explain the observed simultaneity of the rainy season in Central America in north and south locations (Magaña et al , ; Amador et al , ; Amador et al , , ). The mean position during MJ of the ITCZ contributes to the formation of precipitation events in the southern part of Central America.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings help to explain the observed simultaneity of the rainy season in Central America in north and south locations (Magaña et al , ; Amador et al , ; Amador et al , , ). The mean position during MJ of the ITCZ contributes to the formation of precipitation events in the southern part of Central America.…”
Section: Resultsmentioning
confidence: 99%
“…For agriculture, it is the period of the first crops. Prolonged dry conditions during winter, and the start of spring, in addition to an earlier MSD, may have severe implications for the economic and social activities in Central America, as seen during the year 2015 (Amador et al ., , ). In this study, precipitation during MJ is analysed.…”
Section: Introductionmentioning
confidence: 99%
“…The most dominant climate driver in Central America is the North Atlantic Subtropical High (NASH; Taylor and Alfaro, ; Amador et al, ; Amador et al, ) due to the strong easterly trades found on its equatorward flank. Coupled with a strong trade inversion, a cold ocean and reduced atmospheric humidity, the region is generally at its driest condition during the winter.…”
Section: Introductionmentioning
confidence: 99%
“…10A). Este comportamiento estacional coincide con lo reportado por otros autores para la Cuenca Colombiana del Mar Caribe (Amador et al 2006;RuizOchoa, 2011;Ruiz-Ochoa et al 2012;Amador et al 2016), en el cual de mayo a septiembre las aguas muestran su máximo calentamiento. A partir de este último mes y hasta los primeros meses del año el campo térmico superficial experimenta un enfriamiento asociado principalmente a la variación en los campos de viento por la influencia de frentes fríos al final y principio de cada año y menor radiación incidente (Amador et al 2006;.…”
Section: Discussionunclassified